Runtuhnya Kejayaan Kesultanan Turki Utsmani Menurut Teori Filsafat Sejarah Malik Bennabi - Apriliani, Resty; Azmi, Muhammad; Rahuma, Aulia (History Education Department, Universitas Mulawarman, 2024)
The second peak of Muslim glory occurred during the reign of three great empires: the Ottoman, Safavid and Mughal Sultanates in India (Muhammad, 2015). During the reign of Murad I (3rd Ottoman Sultan) 761 AH/359 AD-789 AH/1389 AD, in 2018 he further expanded his territory to the European continent and strengthened internal security. At that time the Ottoman Turks were a nation that dynamic and has extensive knowledge supported by the Sultanate which has a strong army to expand its territory. The greatest success was that the Ottoman Turks managed to occupy the most strategic area, namely Constantinople, which was a strategic area for trade at that time which was located on land between the continents of Asia and Europe. This article aims to examine the cycle of collapse of the Ottoman Empire according to Malik Bennabi's philosophical theory of history. The method used by the author in this article is the historical research method. The historical method used in this article consists of four stages, namely heuristics, verification, interpretation and writing. The results of this research can be concluded that the factors causing the collapse of the Ottoman Turks are in line with Malik Bennabi's theory of civilization which states that the Islamic Ummah experienced modeling because it did not always renew its civilization. At that time, Ottoman Türkiye was satisfied with its glory and was seen as an Empire that was feared by the nation. The reforms that the Sultan wanted to carry out in the military sector at that time were rejected by the imperial army. Thoughts that were not developed and tended to be primitive and satisfied with the achievements that had been achieved were what brought weakness to various aspects of the Ottoman Empire.